2020
DOI: 10.14421/csecurity.2020.3.2.2144
|View full text |Cite
|
Sign up to set email alerts
|

Investigasi Forensik Terhadap Bukti Digital Dalam Mengungkap Cybercrime

Abstract: Teknologi yang berkembang pesat sejalan dengan tindakan cybercrime yang meningkat drastis, sehingga teknik dan modus baru cybercrime sulit untuk dideteksi dan dipecahkan oleh para investigator forensik digital. Tujuan dari penelitian ini adalah memberikan referensi terkait dengan kehandalan tools digital forensic dalam mengungkap cybercrime agar diperoleh bukti digital yang berintegritas, handal dan legal dalam proses ligitasi. Penelitian ini menggunakan metode static forensic dengan framework dari National In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 16 publications
(13 reference statements)
0
8
0
6
Order By: Relevance
“…According to Indonesian regulation about electronic information and transactions law Number 11 of 2008 [6] and Number 8 of 1981 Article 184 [23], explicitly and comprehensively regulated rules in use and transactions of electronics, including digital forensic regulation. In addition, other digital forensics' regulations, such as from the National Institute of Justice (NIJ) [26], National Institute of Standards and Technology (NIST) [23], and other forensic regulations in many countries.…”
Section: Digital Forensics: Digital Breakthroughs To Uncover the Truthmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Indonesian regulation about electronic information and transactions law Number 11 of 2008 [6] and Number 8 of 1981 Article 184 [23], explicitly and comprehensively regulated rules in use and transactions of electronics, including digital forensic regulation. In addition, other digital forensics' regulations, such as from the National Institute of Justice (NIJ) [26], National Institute of Standards and Technology (NIST) [23], and other forensic regulations in many countries.…”
Section: Digital Forensics: Digital Breakthroughs To Uncover the Truthmentioning
confidence: 99%
“…Meanwhile, some cases were found in forensic microbiology [17], DNA analysis from extracted saliva [18], [19], forensic ecology in endangered primates [20], and also contribute to outbreaks [21]. Besides, digital forensics has been used to propose the digitalevidence based, like live forensic analysis on WhatsApp [22] and Web-based [23] also by using Support Vector Machine (SVM) on WhatsApp group [24], biometrics in forensic identification [25], static forensic with the framework from National Institute of Justice (NIJ) [26], Digital Forensic Readiness Index (DiFRI) Models [5], mobile forensics [27], NIST method for Facebook and Instagram investigation [28], and audio forensics [29]. Unique and challenging, a recent study reported that the internet is the most significant way to be a terrorist used [30], [31].…”
Section: Introductionmentioning
confidence: 99%
“…Selain literasi digital, maka diperlukan juga payung hukum yang akan dijadikan landasan hukum atas kasus cybercrime. 12 No. 19 Tahun 2016 tentang " Informasi dan Transaksi Elektronik".…”
Section: Pendahuluan 11 Latar Belakang Masalahunclassified
“…Digital forensics has become an essential part of handling cases in cyberspace. Digital forensics is categorized as a branch of science focusing on taking legal evidence or recognizing it at trial based on data sources from storage media such as hard drives, flash drives, RAM, and others [14]. Along with technology development, it has increased cybercriminals using information technology to support crime using IM applications as a communication medium [15].…”
Section: Introductionmentioning
confidence: 99%